MIMO Passive Control Systems Are Not Necessarily Robust - Jesús U. Liceaga-Castro; Irma I. Siller-Alcalá; Eduardo Liceaga-Castro; Luis A. Amézquita-Brooks (Journal of Control Science and Engineering)
Via several cases of study it is shown that a passive multivariable linear control system, contrary to its single input single output counterpart, may not be robust. Moreover, it is shown that lack of robustness can be exposed via the multivariable structure function.